Education in Age of Global Changes: Threats, Reforms or Drift - Garnyk, Liudmyla Petrivna; Snihurova, Irina Ivanivna (Kharkiv Regional Public Organization "Culture of Health", 2020)
Despite numerous debates issue of balancing between global pragmatism, quality of vocational or higher education and its economic utility (recoupment of capital investment in this area) is still essential for many developing countries and transition economies like Ukraine because of predicted by G. Agamben inevitable "global civil war" has already started.